ANALISIS PEMBERIAN REWARD DAN PUNISHMENT TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN IPA DI SDN 068007 KECAMATAN MEDAN TUNTUNGAN KELAS IV TAHUN PELAJARAN 2022/2023 - Rupina Magdalena Br Tarigan; Eka Talita Br Ginting; Rany Latersia Br Purba (JURNAL CURERE, 2023)
The purpose of this study was to determine the impact of reward and Punishment for students of Public Elementary School 068007 Medan Tuntungan District. Researchers used a qualitative descriptive approach using tests to see science learning outcomes and observations to see student activities. The research location was carried out at Public Elementary School 068007 Medan Tuntungan District in the 2022/2023 Academic Year. The sample of this study were 30 students in class IV Public Elementary School 068007 Medan Tuntungan District. The results showed that giving reward and Punishment had an impact on student learning outcomes where 86.66% completed classically with KKM was 70. Observation results prove that giving reward and Punishment can be one of the strategies used by teachers in learning, this can be seen from the response given by students was very positive and supported by very satisfying learning outcomes. Giving reward and Punishment is used by teachers as a form of reinforcement, a stimulus in educating students. Rewards are given by teachers to students by giving gifts for positive things done by students. Giving rewards is intended to make children more active in their efforts to work and do better. Punishment is given by the teacher to students because students commit violations or mistakes. Punishment will make students regret their wrong actions.